A Novel Ferrocene‐Backboned Unsymmetrical Pincer‐Type Proligand and Its Organotin Derivatives. Issue 13 (15th March 2019) - Gawron, Matthias; Nayyar, Bastian; Krabbe, Christina; Lutter, Michael; Jurkschat, Klaus
Abstract : In this contribution we report the synthesis of the novel unsymmetrical ferrocene‐based pincer‐type proligand η 5 ‐CpFeη 5 ‐C5 H2 ‐1‐Br‐2‐PPh2 ‐5‐CH2 NMe2 (1 ). Its reactivity is demonstrated by isolation of related organotin derivatives η 5 ‐CpFeη 5 ‐C5 H2 ‐1‐SnR3 ‐2‐PPh2 ‐5‐CH2 NMe2 (3, R = Ph; 4, R = Me). The reactions of compounds 3 and 4 with H2 O2 and elemental sulfur gave the corresponding ferrocenylphosphane oxide (5 ) and the sulfides (6, 7 ), respectively. Most remarkably, an unprecedented reaction of the organotin derivative 3 with elemental iodine was observed, providing the ammonium salt [η 5 ‐CpFeη 5 ‐C5 H2 ‐1‐SnPh2 I‐2‐P(O)Ph2 ‐5‐CH2 NHMe2 ]I (8 ). The compounds are characterized by elemental analyses, 1 H, 13 C, 31 P, 119 Sn NMR spectroscopy, electrospray ionization mass spectrometry, and single‐crystal X‐ray diffraction analyses (3–8 ). Also reported are the solid‐state structures of the hydrolysis products [η 5 ‐CpFeη 5 ‐C5 H2 ‐1‐SnPh2 (OH)‐2‐P(O)Ph2 ‐5‐CH2 NHMe2 ]· 0.5H2 O (9a ) and [η 5 ‐CpFeη 5 ‐C5 H2 ‐1‐SnPh(OH)‐2‐P(O)Ph2 ‐5‐CH2 NMe2 ]2 [I3 ]2 (9b ) that were isolated by serendipity. Abstract : No pincer‐type behaviour is observed for the ferrocene derivative 5 and related compounds as only one out of the two donor sites coordinates the tin atom. The high basicity of the aminomethyl nitrogen atom promotes easy hydrolysis of the organotin halide derivatives giving ammonium salts such as 8 and 9a . N··· H··· O hydrogen bridge outperforms intramolecular N→Sn interaction.